Presidential bloopers a hilarious look at our nation's leaders. (Time-Life Video, 1999)
The American President. Powerful. Influential. Well-respected. And sometimes all too human! Laugh along with the presidents as they laugh at themselves in this celebration of the funniest and most down-to-earth moments of the American presidency-a rare, behind-the-scenes look at some of the most outrageous White House wackiness ever captures on video.